Building and Sustaining Optimized Diagnostic Networks to Scale-up HIV Viral Load and Early Infant Diagnosis. (1st July 2020) - Alemnji, George; Peter, Trevor; Vojnov, Lara; Alexander, Heather; Zeh, Clement; Cohn, Jennifer; Watts, Diane Heather; de Lussigny, Smiljka
Abstract : Background: Progress toward meeting the UNAIDS 2014 HIV treatment (90-90-90) targets has been slow in some countries because of gaps in access to HIV diagnostic tests. Emerging point-of-care (POC) molecular diagnostic technologies for HIV viral load (VL) and early infant diagnosis (EID) may help reduce diagnostic gaps. However, these technologies need to be implemented in a complementary and strategic manner with laboratory-based instruments to ensure optimization. Method: Between May 2019 and February 2020, a systemic literature search was conducted in PubMed, the Cochrane Library, MEDLINE, conference abstracts, and other sources such as Unitaid, UNAIDS, WHO, and UNICEF websites to determine factors that would affect VL and EID scale-up. Data relevant to the search themes were reviewed for accuracy and were included. Results: Collaborations among countries, implementing partners, and donors have identified a set of framework for the effective use of both POC-based and laboratory-based technologies in large-scale VL and EID testing programs. These frameworks include (1) updated testing policies on the operational utility of POC and laboratory-based technologies, (2) expanded integrated testing using multidisease diagnostic platforms, (3) laboratory network mapping, (4) use of more efficient procurement and supply chain approaches such as all-inclusive pricing and reagent rental, and (5) addressing systemic issues such as test turnaround time, sample referral, data management, and quality systems. Conclusions: Achieving and sustaining optimal VL and EID scale-up within tiered diagnostic networks would require better coordination among the ministries of health of countries, donors, implementing partners, diagnostic manufacturers, and strong national laboratory and clinical technical working groups.